Reduction strategies for inpatient oral third-generation cephalosporins at a cancer center: An interrupted time-series analysis. - Naoya Itoh; Takanori Kawabata; Nana Akazawa; Daichi Kawamura; Hiromi Murakami; Yuichi Ishibana; Eiichi N Kodama; Norio Ohmagari (PLoS ONE, 2023)
Oral third-generation cephalosporins (3GCs) are not recommended for use owing to their low bioavailability and the risk of emergence of resistant microorganisms with overuse. A standardized and effective method for reducing their use is lacking. Here, in a 60-month, single-institution, interrupted time-series analysis, which was retrospectively conducted between April 1, 2017, and March 31, 2022, we evaluated the effectiveness of a four-phase intervention to reduce the use of 3GCs in patients at a cancer center: Phase 1 (pre-intervention), Phase 2 (review of clinical pathways), Phase 3 (establishment of infectious disease consultation service and implementation of antimicrobial stewardship program), and Phase 4 (educational lecture and pop-up displays for oral antimicrobials at the time of ordering). Although no significant changes were observed in Phases 3 and 4, the first intervention resulted in a significant decrease in the trend and level of days of therapy (DOT) for 3GCs. The level for cephalexin DOT and the trend for sulfamethoxazole-trimethoprim DOT increased in Phase 4, and the trend for amoxicillin and amoxicillin-clavulanate DOT increased in Phase 3. Macrolide DOT showed a decreasing trend in Phases 2 and 4 and decreasing and increased levels in Phases 3 and 4, respectively; no change was observed for quinolones. Actual and adjusted purchase costs of 3GCs decreased significantly during all study periods, while those for oral antimicrobials decreased in Phase 2, and actual purchase costs increased in Phases 3 and 4. No significant reduction in resistant organisms, length of hospital stay, or mortality was observed. This is the first study on the effects of oral 3GC reduction strategies in patients with cancer. We conclude that even facilities that substantially use antimicrobials can efficiently reduce the use of 3GCs.